Structural Dependent Ferromagnetic-Nonmagnetic Phase Change in FePtRu Films - Takashi Hasegawa; Kosuke Ito (Advances in Materials Science and Engineering)
Herein, we studied correlations between crystal structures and magnetic properties of FePt1−xRux films. At room temperature, the chemical disordered A1 films with 0≤x<0.20 and 0.20≤x≤1.00 exhibited ferromagnetic properties and paramagnetic properties, respectively. Curie temperature of the disordered film with x=0.30 was 200 K. In contrast, the ordered L10 films had ferromagnetic properties in a wider range of 0≤x<0.80 with the magnetic easy-axis perpendicular to the film plane. For 0≤x≤0.50, with the ordered structure, the films had high magnetization and high uniaxial magnetic anisotropy of over 107 erg cm−3. For x = 0.60–0.70 with the ordered structure, a temperature-dependent magnetic phase transition appeared, and magnetization reached its maximum value at around 200 K. Using this material system, we proposed a nanopatterning method involving a ferromagnetic-paramagnetic phase change due to the ordered-disordered structural transformation.